Environmental justice and public participation: Implementing source water protection in eastern Ontario - Crane, Natasha (University of Ottawa (Canada), 2009)
Increased public awareness of environmental issues has led to greater public demand for involvement in environmental decision-making. The value of public participation has been recognized by academics and government authorities alike. Relevant public participation and environmental justice literature suggest that successful participation can help to achieve a heightened democratic governance system, uphold citizenship rights and, in turn, reduce environmental injustice. Although some might argue that public participation has already been integrated into the Canadian governance system, it is suggested that the legitimacy of public participation must be solidified with improved regulations and guidelines for process design. This research call is explored through the lens of the Ontario Source Water Protection (SWP) Initiative in the Raisin Region Source Protection Area. As Source Water Protection is ongoing, it provides an outstanding opportunity to observe the implementation of public participation within a decision-making process. Specifically, the objectives of this research were to examine Source Water Protection stakeholder perceptions of public participation and to explore any variation in perceptions that exist between stakeholder groups. Stakeholder groups included SWP Process Architects, SWP Provincial Process Managers, SWP Local Process Managers, and SWP Community Members. Results show that the stakeholder groups have similar understandings of public participation objectives and effective characteristics. At the same time, there was limited understanding of participation design with regards to mobilization strategies, instrument sensitivity and process evaluation. This has resulted in significant differences in stakeholder perception of the Clean Water Act (2006) and the role of the Source Protection Committee. These findings uncover perceived Source Water Protection process strengths and weaknesses, information that can be used to facilitate improvements to public participation practices. In the end, these findings will also help inform public participation processes in other decision-making domains.
Keywords: Geography.; Sociology, Environmental Justice.; Environmental Sciences.